IN VITRO PROPAGATION OF CURCUMA SPAGANIFOLIA GAGNEP., A RARE PLANT SPECIES FROM THAILAND - S. Saensouk; B. Phookabhin; N. Muangsan; T. Chumroenphat; P. Saensouk (Journal of Animal and Plant Sciences, 2023)
Curcuma spaganifolia Gagnep., belonging to the family Zingiberaceae, has attracted widespread attention due to its considerable economic importance. The conventional propagation method for ginger family takes a long time for multiplication due to the low propagation rate and poor seed germination, therefore, tissue culture is an important method for the manipulation of plants for higher propagation. The present study deals with the in vitro and ex vitro conservation of C. spaganifolia Gagnep., a rare plant species from Thailand. Murashige and Skoog(MS) media with different concentrations of plant growth regulators, i.e., cytokinins (benzyladenine (BA) 6-furfurylamino purine (Kinetin), N, phenyl-N’-1,2,3 thidiazole-5-yl urea (TDZ), auxins (indole-3-acetic acid (IAA)), indole butyric acid (IBA) and naphthaleneacetic acid (NAA) were used to study the effect of plant growth regulators for eight weeks. Good development of shoot multiplication was observed in the MS media supplemented with 2 mgL-1 Kinetin, which produced the highest number of shoots per explant (3 shoots/explant) and roots per explant (9.57 roots/explant). Long divided microshoots of C. spaganifolia Gagnep. cultured on liquid MS media supplemented with 2 mgL-1 Kinetin and 1.5 mgL-1 IAA, showed significantly higher numbers of shoots and roots than the undivided microshoot explants. Acclimatization was successful when transplanted into soil, burned rice husk, sand and soil:burned rice husk (1/1 w/w) with 100% survival rate.
Keywords: Curcuma spaganifolia Gagnep.; Plant Tissue Culture; Propagation; Rare Plant; Zingiberaceae